Uso de água salobra, adubação fosfatada e Trichoderma na Cultura da beterraba no maciço de Baturité, Ceará - Barbosa, Andreza Silva (2023)
Due to its increasing commercial exploitation, the study of beets is of great importance, especially with regard to their water and nutritional needs, as well as their responses to abiotic stresses. In the Brazilian semi-arid region, the use of brackish waters for irrigation turns out to be one of the only alternatives to ensure agricultural production during times of drought, causing saline stress, a condition that can negatively affect the growth and productivity of agricultural crops. Living with this problem in semi-arid regions highlights the search for management strategies that reduce impacts on plants and the environment. In this sense, phosphate fertilizer has been tested to mitigate the effects of salinity, as well as the use of fungi of the genus Trichoderma, which increase resistance to abiotic stresses, and consequently, crop productivity. Therefore, the objective was to evaluate the initial growth, gas exchange, productivity and quality of the drink under the use of brackish water and phosphate fertilizer in soil with and without Trichoderma harzianum. The experiment was conducted from August to November 2022, in the experimental area belonging to the University of International Integration of Afro-Brazilian Lusofonia (UNILAB), Redenção-CE. The experimental design used was randomized, in a 3x2x2 factorial scheme, referring to 3 doses of phosphate fertilizer (D1 = 25, D2 = 50 and D3 = 100% of the recommended dose of phosphorus), with and without the use of Trichoderma harzianum and two levels of electrical conductivity of the control water (A1= 0.5 dSm-1 and A2= 6.2 dSm-1). The following evaluations were carried out: plant height (AP), number of leaves (NF), leaf area (AF), net CO2 assimilation rate (A), transpiration (E), stomatal conductance (gs) internal CO2 concentration (Ci), leaf temperature (TL) and intrinsic water use efficiency (EIUA) at 37 days after transplanting (DAT). At 80 DAT, tuberous root diameter (DRT), tuberous root length (CRT), tuberous root mass (MRT), productivity (PRO), shoot dry mass (MSPA), tuberous root pH were evaluated. (pH) and soluble solids content (°Brix). Phosphate fertilizer at doses of 50 and 100% of the recommendation was more efficient for plant height, number of leaves, leaf area, dry mass of the aerial part, mass of the tuberous root, length and productivity of the tuberous root. A dose of 50% of the phosphorus recommendation mitigated saline stress and provided greater dry mass of the aerial part. Saline stress negatively reduced leaf area and stomatal conductance and increased leaf temperature. Fertilization with 25% of the recommended phosphorus, under lower saline levels and absence of Trichoderma, provides a higher photosynthetic rate and transpiration. Saline stress affects photosynthesis and transpiration, but with less intensity at a dose of 25% of the P recommendation, in soil with Trichoderma. The highest leaf temperature was at a dose of 25% of the phosphorus recommendation in the presence of Trichoderma and in water with lower salinity.